The Association between Platelet Count and Acute Phase Response in Chronic Spontaneous Urticaria - Kasperska-Zając, Alicja (Hindawi Publishing Corporation, 2014)
Background. The platelet parameters and C-reactive protein (CRP) are markers reflecting a systemic inflammatory response. Among those, CRP is one of the major proteins helpful in determination of severity/activity of chronic spontaneous urticaria (CSU). Aim. To determine relationships between platelet activation indices and serum concentration of CRP, the best marker of acute phase response, and their potential clinical use in CSU patients. Methods. Mean platelet volume (MPV), platelet distribution width (PDW), and platelet count as well as serum CRP concentration were measured in CSU patients, showing different degrees of urticarial severity, and in the healthy subjects. Results. No significant differences were found in MPV and PDW between CSU group and the healthy subjects. The platelet count was significantly higher in moderate-severe CSU than that of the controls and mild CSU patients. Serum CRP concentrations were significantly higher in CSU patients as compared with the healthy subjects and significantly correlated with the platelet count in CSU patients. Conclusions. Acute phase response in CSU is associated with the increased number of circulating platelets in patients with more severe symptoms. It seems that simple determination of platelet size indices is not a reliable indicator of CSU severity/activity.